Association between Modic changes and recurrence of lumbar disc herniation after percutaneous endoscopic lumbar discectomy: a meta-analysis - Li, Xianfeng; Ren, Honghong; Peng, Lipeng; Yuan, Jiaqin (Frontiers in Surgery, 2025)
PurposeThis study aims to identify the association between preoperative Modic changes and the recurrence of lumbar disc herniation (LDH) in patients who have undergone percutaneous endoscopic lumbar discectomy (PELD).MethodsThe PubMed, Web of Science, EMBASE, and CNKI databases were searched from their inception until 19 March 2025. Early recurrence was defined as herniation occurring within 6 months postoperatively, whereas late recurrence referred to herniation occurring after 12 months. Odds ratios (ORs) with 95% confidence intervals (CIs) were combined, and subgroup analyses were conducted according to the recurrence type.ResultsTwenty-seven studies involving 10,116 patients were included, with the majority of studies originating from China (25/27). The recurrence rates for patients without and with Modic changes were 7.44% and 16.41%, respectively (type I: 15.01%; type II/III: 18.14%; P < 0.001). The presence of Modic changes was associated with a significantly increased risk of recurrence (OR = 2.96, 95% CI: 2.29–3.82, P < 0.001), and subgroup analyses by the recurrence period (early or late) showed consistent findings. However, patients with Modic type II/III changes did not have a higher risk of recurrence than those with Modic type I changes (OR = 1.13, P = 0.217).ConclusionPreoperative Modic changes are associated with postoperative recurrence among LDH patients undergoing PELD, and the presence of Modic changes is related to a significantly higher risk of early and late recurrence.